ANALISIS FAKTOR-FAKTOR MOTIVASI DALAM BELAJAR BAHASA INGGRIS PADA KELAS 11 SMAN 6 BENGKULU: Analysis of Motivational Factors in Learning English Classroom at Eleventh Grade SMAN 6 Bengkulu - Andriyani, Kiki; Nurcholis, Ivan Achmad (PUAN INDONESIA, 2024)
This research aims to explore what factors motivate students to learn English. Data collection was carried out through a qualitative descriptive approach with instruments in the form of observations, namely making observations during the research. Apart from that, interviews were used to find out other factors outside existing theories. Analyze data using analysis descriptive with interviews and observation of data that is reduced and presented. Results Research shows that as many as 50% choose teachers as motivational drivers in learning English in class and the rest choose to give rewards and punishments, give tests or exams and the last factor is goals or desires.